2024
DOI: 10.5772/intechopen.113084
|View full text |Cite
|
Sign up to set email alerts
|

Approaches of Milking Biosecurity and Milking Parlour Hygiene in Dairy Farms

Georgeta Stefan,
Stelian Baraitareanu

Abstract: Control of diseases in dairy farms is based on various management factors, such as separation of dairy farms from other domestic and wild animal species, control of human circulation and contact with cows, cleaning and disinfection of vehicles, equipment, surfaces, and other unanimated secondary sources of contamination, feed and water hygiene, waste management, and management of technological processes (e.g., calving management, colostrum management, and milking management). In dairy farms, the milking parlou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A previous article by Stefan and Baraitareanu [ 24 ] suggested that to prevent pathogen proliferation in dairy farms, milking parlour surfaces should be cleaned and disinfected twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…A previous article by Stefan and Baraitareanu [ 24 ] suggested that to prevent pathogen proliferation in dairy farms, milking parlour surfaces should be cleaned and disinfected twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that milk has its own defense systems against bacteria, such as its microbiota whose populations act antagonistically against pathogenic intruders [8,9]. But even these defense systems succumb to various factors such as the environmental temperature, the environmental spoilage, the welfare of the animals, the sanitation of the milking apparatus and of the milking process, and the health of the udders and of the animals, to name a few [10][11][12][13][14][15][16][17][18]. Contaminated milk in the bulk tank is a common finding [19][20][21].…”
Section: Introductionmentioning
confidence: 99%